Contribution of Particles Size Ranges to Sand Friction - Mostefa Kara, E.; Meghachou, M.; Aboubekr, N. (Engineering, Technology & Applied Science Research, 2013)
This work studies the correlation between certain physical properties of granular material such as the friction angle and the grain size distribution. In the laboratory, the determination of friction angle requires hard and expensive testing. Prediction of this parameter from the grading curve proves to be very interesting. Direct shear tests were performed on actual marine sand of Tergha (Algeria) and on seventeen different samples arranged from the same sand with various particle size ranges. Results showed that the friction angle of sand is a result of contribution of various constituent granular classes.